Modeled and measured fluxes of latent and sensible heat and snow transport at S17 near Syowa in Antarctica ... - Sigmund, Armin; Melo, Daniela Brito; Dujardin, Jérôme; Lehning, Michael (EnviDat, 2025)
This dataset supports a related publication (Sigmund et al., 2025) and contains - results of four **large-eddy simulations** (LES) coupled to a Lagrangian model (LM) for snow transport, aiming to reproduce field measurements, especially latent heat fluxes, at the S17 site near Syowa Station, East Antarctica, in conditions of drifting and blowing snow, - references to the **source code** of the LES-LM model, - the source code and results of a simple **one-dimensional (1D) model** inspired by the large-scale model CRYOWRF (Sharma et al., 2023), aiming to reproduce the LES-LM results, - post-processed **measurements** shown in the figures of the related publication, - **programming code** for post-processing and plotting the results. The LES-LM simulations solve the Navier-Stokes equations for incompressible flows and advection-diffusion equations for air temperature and specific humidity in a domain of 19.2 x 18.32 x 18.32 m³. In these simulations, the airflow is driven by a prescribed large-scale pressure ...